Allied health use among women with incident Parkinson’s disease: Population-based findings from the Australian Longitudinal Study on Women’s Health - Paul, Serene; Wong, Cassandra; Allen, Natalie; Dennis, Sarah; Cavenagh, Dominic; Dolja-Gore, Xenia (International Journal of Population Data Science, 2026)
Background Allied health interventions benefit people with Parkinson’s disease (PD) by reducing symptom severity and improving mobility, mood and quality of life. Yet current evidence suggests low and delayed uptake of allied health among this population. This study aimed to determine the proportion of Australian women with incident PD who accessed allied health and when they did so following diagnosis. Methods Participants of the Australian Longitudinal Study on Women’s Health who consented to data linkage were included. From national medication dispensing data, incident PD cases were identified as those taking anti-parkinsonian medications for at least 3 months following a 12-month lookback period. Their allied health use was identified from national primary health and aged care datasets and from hospital admission data from all states and territories. Results A total of 781 women with incident PD were identified between 2003-2022. Sixty-one percent (n=477) accessed at least one allied health discipline following diagnosis, with a median time to first use of 282 days (interquartile range 72–880). Half (55%) who accessed allied health did so within one year of diagnosis, with up to 19% showing delayed access >3 years after diagnosis. Discussion Despite evidence-based recommendations that people with PD should be referred to allied health upon diagnosis, many are not accessing such care, potentially contributing to the high disability associated with PD. Improving patient education (e.g. through public health campaigns and Parkinson’s organisations) and proactive referrals by physicians may improve access and reduce disability for people with PD.